Glossary of geology - Neuendorf, Klaus K. E.; Mehl, James P.; Jackson, Julia A., 1939- (American Geological Institute, 2011)
Contains nearly 40,000 entries, including 3,600 new terms and nearly 13,000 entries with revised definitions from the previous edition. The revisions represent both advances in scientific thought and changes in usage and they make this 800+ page hardbound a must for any earth science professional or student. In addition to definitions, many entries include background information and aids to syllabication. The Glossary draws its authority from the expertise of the more than 100 geoscientists in many specialties who reviewed definitions and added new terms. --from publisher description
Keywords: Geology -- Dictionaries.; elektronické knihy; electronic books